Evaluation of the Effectiveness of Biofilter Columns with Mixed Media for Tofu Liquid Waste Treatment - Tazkia Maulida Putri; Zahwa Annaya; Mutiara Dewi Rukmana; Silvia Devi Eka Putri; Istiqomah Rahmawati (JOBC, 2025)
Indonesia's increasing number of tofu industries has led to a rise in waste volume from this sector, requiring exceptional management. Tofu wastewater, a byproduct of tofu production that is no longer utilized, contains a high concentration of organic matter and can adversely affect water supplies if discharged untreated. This study aims to investigate an efficient filtration technique using filtration media for processing tofu wastewater. The biofilter column used in this study was made from a Le Minerale gallon and comprised layers of zeolite, bio balls, bearings, and activated charcoal to filter and purify the water from organic substances. The results showed that while filtration effectively reduced Total Dissolved Solids (TDS) from 995 ppm to 129 ppm after the fourth filtration, it was ineffective in neutralizing the pH of the tofu wastewater, which remained at pH 4 before and after filtration. This indicates that the wastewater remains acidic and cannot be directly discharged into the environment. Additionally, conductivity and salt levels increased after multiple filtrations, possibly due to ion release from the filter materials or saturation effects. This study reveals that the column configuration and filtration materials used were ineffective in removing acidic components from tofu wastewater. Therefore, design adjustments and filtration media selection are needed to achieve better results in treating tofu wastewater.